Effect of quaternary benzo[c]phenanthridine alkaloids sanguilutine and chelilutine on normal and cancer cells - Slunská, Z; Gelnarová, E; Hammerová, J; Táborská, E; Slaninová, I (Toxicology in vitro, 2010)
Sanguilutine and chelilutine, quaternary benzo[c]phenanthridine alkaloids, were studied for their antiproliferative activities with regard to their ability to induce oxidative stress. We observed potent antiproliferative activities for both alkaloids against three tumour (HeLa; HL-60; A-2780) and two normal (V-79; LEP) cell lines. Both alkaloids were efficient inductors of apoptosis. Statistical analysis revealed higher toxicity for sanguilutine compared to chelilutine and unequal sensitivity with regard to individual cell lines, although independent of the character of the cell line (i.e. tumour vs. normal). Dihydrofluorescein diacetate staining was used to measure intracellular ROS accumulation after treatment with sanguilutine, chelilutine, sanguinarine, and chelerythrine. In addition, anti-oxidative effects were studied. The effects of the alkaloids were compared with the effects of commonly used anti-oxidants, such as trolox, caffeine acid, and chlorogenic acid. None of the tested alkaloids (0.1 and 1 microg/ml) increased ROS production. Pre-incubation of sanguinarine and chelilutine (at all tested concentrations) and sanguilutine and chelerythrine (1 microg/ml) decreased oxidative stress caused by H(2)O(2). These findings indicate high antiproliferative and pro-apoptotic effects of sanguilutine and chelilutine that are not accompanied by oxidative stress induction, to the contrary, both alkaloids showed anti-oxidative effects.
Keywords: Oxidative Stress; Tetrazolium Salts; Coloring Agents; reaktivní formy kyslíku; oxidační stres; Humans; benzofenantridiny; Cell Cycle; koncové značení zlomů DNA in situ; tetrazoliové soli; In Situ Nick-End Labeling; Antineoplastic Agents; annexin A5; Benzophenanthridines; oxidancia; lidé; proliferace buněk; Reactive Oxygen Species; fragmentace DNA; apoptóza; Annexin A5; thiazoly; Hydrogen Peroxide; Propidium; peroxid vodíku; propidium; Cell Proliferation; barvicí látky; DNA Fragmentation; nádorové buněčné linie; protinádorové látky; Oxidants; Thiazoles; Cell Line, Tumor; buněčný cyklus; Apoptosis